Effects of aerodynamic drag and drafting on propulsive force and oxygen consumption in double poling cross-country skiing - Ainegren, M.; Linnamo, V.; Lindinger, S. (Medicine & Science in Sports & Exercise, 2022)
Purpose This study aimed to investigate the effects of aerodynamic drag and drafting on propulsive force (FPROP), drag area (CDA), oxygen cost (V?O2), metabolic rate (E?), and heart rate (HR) during roller skiing on a treadmill in a wind tunnel using the double poling technique. A secondary aim was to investigate the effects of wind versus no-wind test conditions on the same physiological parameters.